Functional outcome of intra-articular fracture of distal end of radius treated by open reduction and internal fixation with locking distal radius system - Kumar Chandan; Ravi Kumar; Rahul Ranjan; Rohit Amar (Journal of Orthopaedic Diseases and Traumatology, 2021)
Background: There is alays been a dilemma in the treatment of intra-articular distal radius fracture (DRF). Close reduction and cast application gives satisfactory result in extra-articular Distal Radial Fractures but there is alays been debate beteen open and close reduction in the intra-articular fracture. Hence, this study is to evaluate effectiveness of open reduction and internal fixation of intra-articular Distal Radial Fractures. Materials and Methods: This prospective observational study as carried out in the department of orthopedics, All India Institute of Medical Sciences, Patna, from August 2016 to March 2019. The patient ere included ho qualified the inclusion criteria. The included patient ere treated by open reduction and internal fixation ith distal radius plate. The outcome as assessed in term of anatomical variables (radial dorsal tilt, length, and angle), residual deformity, and subjective result evaluation using Sarmiento's modification of Lind Storm criteria. The complication if any as also noted. Results: This study included 30 cases of intra-articular DRF, 12 fractures of AO type B, and 18 fractures of AO type C. Anatomically, 24 patients (80%) had excellent restoration of anatomy, 4 patients (13%) had good restoration and 2 had fair (7%) restoration of anatomy. 93% of patients had excellent to good alignment of fragments and good reduction could not be achieved in 7% of patients resulting in fair or poor results. Functionally, 22 patients (73%) had excellent, 5 good (17%), and 3 patients had fair (10%) restoration of functions. Conclusion: Open reduction and internal fixation ith volar plate and scres fixation gives satisfactory (good to excellent) result in intra-articular Distal Radial Fractures.